PENGEMBANGAN KOMPETENSI MATEMATIKA MELALUI KEGIATAN KEBHINEKAAN: STUDI KASUS PEMBELAJARAN MAHASISWA MELALUI MODUL NUSANTARA PERTUKARAN MAHASISWA MERDEKA DI LEMBAH TUMPANG - Setiawan, Rudy; Anwar, Moh. Farid Nurul (JURNAL ILMIAH PENDAS: PRIMARY EDUCATION JOURNAL, 2024)
This research discusses the development of mathematical competence through diversity activities, focusing on student learning through the Nusantara Module in the Independent Student Exchange Program in the Tumpang Valley. The background of this research is rooted in the importance of improving the quality of mathematics education and strengthening the values of diversity in the university environment. The purpose of this study was to investigate the effectiveness of Nusantara Module in improving the understanding and mathematical skills of students from various cultural and ethnic backgrounds. The research method used is a qualitative approach with interview, observation, and documentation analysis techniques. The results showed that learning through the Nusantara Module succeeded in building a deep understanding of mathematics and problem-solving skills among students, while appreciating cultural diversity. In addition, there is an increase in active participation, creativity, and enthusiasm for student learning in the context of diversity. In conclusion, the Nusantara Module in the context of the Independent Student Exchange Program not only improves mathematical competence, but also strengthens understanding of the values of diversity and cross-cultural cooperation. These findings provide the basis for the development of diversity-based learning strategies in higher education, supporting students' academic and social growth in a multicultural atmosphere.